A predictive nature for tactile awareness? Insights from damaged and intact central-nervous-system functioning - Pia, Lorenzo; Garbarini, Francesca; Burin, Dalila; Fossataro, Carlotta; Berti, Anna (Frontiers in Human Neuroscience, 2015)
In the present paper, we will attempt to gain hints regarding the nature of tactile awareness in humans. At first, we will review some recent literature showing that an actual tactile experience can emerge in absence of any tactile stimulus (e.g., tactile hallucinations, tactile illusions). According to the current model of tactile awareness, we will subsequently argue that such (false) tactile perceptions are subserved by the same anatomo-functional mechanisms known to underpin actual perception. On these bases, we will discuss the hypothesis that tactile awareness is strongly linked to expected rather than actual stimuli. Indeed, this hypothesis is in line with the notion that the human brain has a strong predictive, rather than reactive, nature.